What happened to harmonization of the PTSD diagnosis? The divergence of ICD11 and DSM5. (22nd April 2013) - Bisson, J. I.
Abstract : The development of ICD11 and DSM5 was seen as an opportunity to harmonize the two major classification systems for mental disorders. The proposed ICD11 and DSM5 diagnostic criteria for PTSD are markedly different. The implications of this remain to be seen, but have the potential to cause confusion to PTSD sufferers, clinicians, researchers and others impacted on by the condition.